An acute ischemic stroke after multiple bee stings in an elderly patient - Rachaiah, Niranjan Mambally; Kalegowda, Rajashekar Hirisave; Krishnaswamy, Rashmi Bhadravathy (Asian Journal of Medical Sciences, 2013)
Although bee stings can cause local and systemic allergic reactions, neurological complications are rare. There are few reports of stroke following bee or wasp stings. We report a 70-year-old healthy man developed a focal neurologic deficit 5 hours after multiple bee stings, which was confirmed to be an acute ischemic stroke on computed tomography (CT) scan. DOI: http://dx.doi.org/10.3126/ajms.v4i2.7892 Asian Journal of Medical Sciences 4(2013) 55-58